Preferences for Hybrid Learning of Postgraduate Students - Yeli, Salmaini; Hartono; Kasmuri; Nasution, Syamruddin (International Journal of Scientific Research and Management (IJSRM), 2023)
This paper aims to describe the preferences of postgraduate students regarding hybrid learning and the factors that influence their preferences for this learning model. This is considered important because postgraduate students are mature individuals and have the right to determine the learning process that suits their needs. Therefore, this research is a quantitative descriptive study. The research sample consisted of 204 postgraduate students from Sultan Syarif Kasim State Islamic University of Riau, including master's and doctoral programs. Sampling was carried out using a quota random sampling technique without distinguishing between study programs. The research instrument used was a closed questionnaire. Data analysis was conducted using descriptive statistics in the form of tables and diagrams. The results showed that of the total respondents, 8 students (4%) had a very strong preference for hybrid learning, 165 people (81%) had a preference in the good category, 13 people (6%) had a poor preference, 15 people (7%) had an unfavorable preference, and only 3 people (1%) had a very unfavorable preference for hybrid learning. Factors that influence postgraduate students' decisions to choose hybrid learning include the availability of resources for online learning, as well as the provision of complete and varied online learning resources.